EFFECT OF LEADERSHIP STYLES ON JOB PERFORMANCE AMONG SECONDARY SCHOOL TEACHERS - Atif Rafiq; Dr. Tariq Mahmood Khan; Mirza Muhammad Afzal Baig (PalArch's Journal of Archaeology of Egypt / Egyptology, 2022)
The growth of the educational institutions mainly depends on the performance of academic staff. The major objective of this research was to determine the effect of leadership styles on job performance of the secondary school teachers. The population was public secondary school teachers in Faisalabad whereas, 237 participants were selected for sample of the study through simple random sampling techniques. For data collection, it was administered standardized questionnaire based on variables of the study such as; transformational and transactional leadership styles and job performance. The collected data analyzed by using SPSS-25 according to the research questions proposed in this research. The findings of the study indicated that there was positive and significant association between leadership styles and job performance. Furthermore, it was found that there was a positive and significant effect of leadership styles on job performance of secondary school teachers. This study may be helpful to adopt the best fit leadership styles according to the situation for educational leaders.